2021
DOI: 10.3390/su13147884
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Indoor Living Wall System on Air Quality: A Comparative Monitoring Test in Building Corridors

Abstract: Living wall systems have been widely recognized as one of the promising approaches for building applications due to their aesthetic value and ecological benefits. Compared with outdoor living wall systems, indoor living wall systems (ILWS) play a more vital role in indoor air quality. The aim of this study is to investigate the effects of ILWS on indoor air quality. In an office building, two parallel corridors were selected as comparative groups. A 10.6 m2 ILWS was installed on the sidewall of the west corrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 53 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…For example, plant transpiration increases indoor relative humidity by 9-12% [10]. This may be favorable for indoor comfort in arid regions but could be disadvantageous in hot and humid regions [15]. Other considerations include the noise made by hydroponic systems [16], a minor chance of discomfort as a result of allergies [17], and energy consumption and heat dissipation caused by the artificial growth lights [18].…”
mentioning
confidence: 99%
“…For example, plant transpiration increases indoor relative humidity by 9-12% [10]. This may be favorable for indoor comfort in arid regions but could be disadvantageous in hot and humid regions [15]. Other considerations include the noise made by hydroponic systems [16], a minor chance of discomfort as a result of allergies [17], and energy consumption and heat dissipation caused by the artificial growth lights [18].…”
mentioning
confidence: 99%
“…When only 2.5 modules were added, the improvement in increasing the chamber humidity level was only 76.92 %. This relative humidity elevation was directly proportional to the analysis of Shao et al in offices of 3.1-6.4 % (Shao et al, 2021b).…”
Section: Discussionmentioning
confidence: 70%
“…The results are consistent with the results obtained in several investigations, where the effect of installing green walls on IAQ was studied. Tudiwer & Korjenic [7], found a decrease in CO 2 in a study carried out in a school building in Vienna, Austria; Peterková et al [8] also observed a decrease in CO 2 concentrations in a classroom at the Faculty of Civil Engineering at the Technical University of Brno, Czech Republic; Pettit et al [9], in a school in Beijing, observed a decrease in VOCs concentrations; and Shao et al [10], at a university in China, observed a reduction in CO 2 and PM 2.5 levels after installing a green structure in a small corridor.…”
Section: A Indoor Air Monitoringmentioning
confidence: 96%